Intrinsic and Extrinsic Motives Support Adults’ Regular Physical Activity Maintenance - Geller, Karly; Renneke, Kate; Custer, Sarah; Tigue, Grace (Sports Medicine International Open, 2018)
Motives for physical activity were compared between adults who either successfully or unsuccessfully maintained regular physical activity over the last 10 years. Adults age 28–45 (N=721) completed an online survey, reporting their current physical activity levels and self-determination theory (SDT) motives, as well as their physical activity levels at least 10 years prior. With participants’ current and retrospective reports of their physical activity, four sample subgroups were created, including maintainers, improvers, decliners, and sedentary. ANOVA analyses were used to examine differences in motives between physical activity maintenance groups. Those who successfully maintained regular physical activity (maintainers) reported higher intrinsic and extrinsic motives compared to those who were not regularly active (P<0.05). Interestingly, maintainers reported similar physical activity motives compared to those who reported increased physical activity over time. Among the current sample and consistent with theory, motives for physical activity significantly influenced participants’ long-term maintenance of regular physical activity. Future interventions should consider these constructs to promote sustained physical activity.
Keywords: Self-determination theory; Habitual behaviour; Motivation; Physical activity; Maintenance